Transcutaneous electrical nerve stimulation over acupoint for chronic obstructive pulmonary disease: A systematic review and meta-analysis - Wei, Ying; Yuan, Nairong; Dong, Yan; Wang, Lixia; Ding, Jiru (Frontiers in Public Health, 2022)
Background: Transcutaneous electrical nerve stimulation over acupoint (acu-TENS), a new technique applied in pulmonary rehabilitation programs, has been gradually used in the management of chronic obstructive pulmonary disease (COPD). However, the effects of acu-TENS have not been fully evaluated. Therefore, this review was conducted to assess the effects of acu-TENS for COPD. Methods: Seven electronic databases were searched from their inception to September 2021 for randomized controlled trials of acu-TENS for COPD. Two investigators independently performed data extraction and methodological quality assessment. Heterogeneity was examined by Cochrane X2 and I2 tests. The source of heterogeneity was investigated by subgroup analysis or sensitivity analysis. Results: Ten studies between 2008 and 2021 were included in our review. The aggregated results indicated that acu-TENS showed positive effects in forced expiratory volume in one second (FEV1) [MD = 0.13L, 95%CI (0.11 to 0.16), P＜0.00001], FEV1% predicted [MD = 5.92%, 95%CI (3.43 to 8.41), P＜0.00001], 6-min walk distance (6MWD) [MD = 14.68m, 95%CI (6.92 to 22.44), P = 0.0002], dyspnea visual analogue scale (DVAS) [MD = -7.58, 95%CI (-14.33 to -0.84), P = 0.03], modified Borg scale (MBS) [MD = -0.46, 95%CI (-0.86 to -0.06), P = 0.03], and COPD assessment test (CAT) [MD = -4.25, 95%CI (-5.24 to -3.27), P＜0.00001]. Six studies reported adverse effects, with only one patient had shoulder pain after acu-TENS. Conclusions: Acu-TENS seems to be effective in improving pulmonary function and health status in patients with COPD, with little effect on exercise capacity and dyspnea. However, this result should be interpreted with cautious, and high-quality RCTs were needed for further verification.